Noise-induced escape flux on time-scales preceding quasistationarity - Soskin, S.M.; Sheka, V.I.; Linnik, T.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Noise-induced escape from the metastable part of potential is considered on time scales preceding the formation of quasiequilibrium within that part of the potential. It is shown that, counterintuitively, the escape flux may depend exponentially strongly, and in a complicated manner, on time and friction.